Genetic diversity of Trichoderma spp. isolated from alkaline pistachio soils using morphological and molecular characteristics - Hossein Alaei; Fahimeh Mirkhani; Amirhossein Mohammadi; Masoumeh Haghdel (Journal of Advances in Plant Protection)
The genetic diversity of Trichoderma species isolated from pistachio soils in Kerman Province was investigated. A total of 131 isolates were obtained and identified at the species level by analyzing their morphological characters. Eighty-seven isolates were identified as Trichoderma harzianum and forty-four isolates as Trichoderma aureoviride. The sequences of their ribosomal RNA (rRNA) gene internal transcribed spacers (ITS), were determined and used as phylogenetic markers. The complete ITS nucleotide sequences of 17 selected isolates of T. harzianum and T. aureroviride were determined. Minimal rDNA-ITS sequence variation was observed, and molecular informative differences between T. harzianum and T. aureroviride were not found in phylogenetic analysis.. RAPD-PCR using the four random primers, OPA4, OPA3, A-5, and Pr3, was evaluated as a technique to separate and differentiate these two species. The four primers produced DNA bands for the 16 Trichoderma isolates, of which 81 (95.3%) were polymorphic, and four (4.7%) were monomorphic. The RAPD data was computed into a similarity matrix using the NTSYS computer program. The genetic similarity coefficient between pairwise isolates varied from 0.50 to 0.98 based on an unweighted paired group method of arithmetic average (UPGMA) cluster analysis. The results showed that all isolates were grouped into two main clades. In agreement with observation, data from morphological characteristics resulting in RAPD-PCR banding patterns revealed it was easier to identify and differentiate T. harzianum and T. aureroviride isolates. The RAPD-PCR technique was practical and efficient for routine high-resolution diversity studies for the two species.